A rational utilization of scarce planting materials in cassava (Manihot esculenta) - OSAKWE, J O; IKPE, F N; ADENIJI, M A; FOLORUNSO, D O (The Indian Journal of Agricultural Sciences, 2013)
A study was conducted during 1996-97 to examine a rational utilization of scarce planting materials together withgrowth qualities of cassava (Manihot esculenta Crantz)'TMS 91934' using 6 cuttings: 25 cm, 20 cm, 15 cm, 10 cm, 5cmand the proximal portion approximately 8 cm as treatment. Plants derived from 15 cm length had the best growthcharacteristics: highest sprout count (100%), comparable number of nodes activated into growth. The highest incidenceof cassava mosaic disease was recorded in 25 cm length (76.6%) while the least was recorded in 5 cm length (50.0%).With regard to cassava bacterial blight incidence and severity, there was a substantial increase in both parametersfrom 1 month after planting up till 3 months after planting, thereafter, there was a gmdual decline in the same. Thehighest fresh tuber weight was recorded in 15 cm length (37.87 tonnes/ha) followed by 25 cm (33.97 tonnes/ha) while5 cm had the least fresh tuber weight (23.34 tonneslha). The use of 15 cm cuttings was found to increase multiplicationratio, economize on scarce planting material and to reduce foilar diseases as well as increase tuber yield of cassava. Cuttings shorter than 15 cm should not be used as planting material due to its susceptibility to rapid desiccation and inability to give up to 2 nodes which may be actvated into growth.